Effect of Situational Leadership Style on Com petence and Employee's Performance of Cleaning Agency at South Jakarta City - Indira Santi Kertabudi (Universal Institute of Professional Management, 2022)
This study purpose is to determine and assessing employee's performance of Cleaning Agency at South Jakarta City because there is issused South Jakarta cleanliness is still not good The condition is likely caused by leadership style and employee's competence who have not been good as well so the impact of employee's performance implementation. This study uses path analysis to determine the effect of leadership style on employee's competence and employee's performance. The population are 289 employee's of Cleaning Agency at South Jakarta City Total 100 samples represents the four villages with clean and dirty categories. The results chowed that situational leadership style has been able to improve the employee's competence. Better situational leadership style can increase the employee's competence, which in turn can improve employee's performance.